We need to change our attitude, and journals can help: Reflections in response to Spiller & Olff (2018) - Ineke Wessel; Helen Niemeyer (European Journal of Psychotraumatology, 2019)
Adopting Registered Reports is an important step for the European Journal of Psychotraumatology to promote open science practices in the field of psychotrauma research. However, adopting these practices requires us as individual researchers to change our perspective fundamentally. We need to put fears of being scooped aside, adopt a permissive stance towards making mistakes and accept that null-results should be part of the scientific record. This is difficult because the culture in academia is competitive. Incentives are on publishing novel and positive results in high impact journals. A change in journal policies, such that openness and transparency are reinforced, can facilitate an attitude change in individual researchers.